The rubic's cube approach a multi-dimensional model for working with children - Arellano-Carandang, Ma. Lourdes (Philippine Journal of Psychology, 1981)
This paper discusses a multi-dimensional model which may be used in the treatment of behavioral and emotional problems among children. The model proposes that for any therapy to be effective, the various dimensions along which a child may develop must be considered. The four dimensions laid down are the following: first, the child must be viewed as a total person (i.e., the five aspects of his development must be considered - intellectual, emotional, physical, social and moral or spiritual); second, the child's developmental level must be considered (i.e., the stage of development that the child is in at the moment, considering each of the five aspects of his total personality); third, the context of the problem must looked at (i.e., the child's behavior must be viewed in the context of the family and the community); and fourth, the child's inner world, or the child's own perception of his stressful situation must be looked at. Case studies are presented to illustrate each of these dimensions.